Analisis Kepuasan Mahasiswa terhadap SOP Terintegrasi: Upaya Harmonisasi ISO 45001:2018 dan ISO 14001:2015 Menuju Green Laboratory - Kadek Adi Mahendra; I Made Dwi Mertha Adnyana (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The Highway Laboratory carries significant occupational safety risks and environmental impacts; however, the implementation of standard operating procedures (SOPs) that integrate occupational safety and environmental management aspects remains suboptimal. This study aims to analyze student satisfaction levels toward integrated SOPs based on ISO 45001 and ISO 14001 as an effort to harmonize toward a green laboratory in the Highway Laboratory. This study employed a descriptive quantitative approach using a survey method involving 150 Civil Engineering students from the 2023 cohort who had completed the full series of laboratory practicum sessions. Data were collected using a structured questionnaire consisting of 30 statement items across six measurement dimensions and analyzed using descriptive statistics. The results revealed that the overall student satisfaction level fell into the